Manuscript: "Making Up Missed Fasts in the Year of Omission" (Verification) By Sayyid Hassan bin Hadi Al-Sadr Al-Mousawi Al-Kadhimi (1272 AH - 1354 AH( (Journal of the College of Basic Education, 2026)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the most honorable of creation and messengers, Muhammad and his pure and immaculate family. In the name of God, the Most Gracious, the Most Merciful: (It is He who has sent His Messenger with guidance and the religion of truth to manifest it over all religion. And sufficient is God as Witness), God Almighty’s truth (Surat Al-Fath: 28). Fasting is the third pillar of the Islamic religion, and it is a spiritual act of worship of the first degree. It is a sign and evidence of the extent of a Muslim’s sincerity, honesty, and submission to the commands of Allah Almighty: So righteousness is the true meaning of this spiritual act of worship, and this act of worship has conditions, and without them there will be a defect, including the period of fasting. May Allah Almighty make us among those who hear the command and follow the best of it. In this religious research that I am placing in your hands, I am talking about an important religious jurisprudential issue in the belief and life of Muslims, which is (making up fasts), and what it includes. It is a request from Professor Sayyid (may his secret be sanctified) to follow up on the sayings of scholars regarding the rulings on making up fasts for days of the holy month of Ramadan after a year and how to perform them and what results from that, and other rulings related to them mentioned in the issue, which every Muslim man and woman must be keen to learn. In this research, I relied on the mothers of jurisprudential books of the Imami school, in verifying this manuscript.